Differential Pulse Anodic Voltammetric Determination of the Pharmaceutical Compound Pramipexole Dihydrochloride in its Tablets - Zayed,Sayed I. M. (2017)
The electrochemical behavior of pramipexole dihydrochloride was studied at carbon paste electrodes in 0.04 M Britton-Robinson buffer of pH 6.08, using cyclic and differential pulse voltammetric techniques. The oxidation of pramipexole dihydrochloride is an irreversible diffusion-controlled process. A differential pulse anodic voltammetric procedure has been developed for determination of the drug over the concentration range of 1.20 - 8.23 μg/mL, with detection and quantification limits of 0.21 and 0.68 μg/mL, respectively. The proposed method was successfully applied for the determination of the drug in its commercial tablets.